Effect of counterions on the micellization and monolayer behaviour of cationic gemini surfactants. Issue 17 (10th April 2017) - Islam, M. S.; Shortall, S. M.; Mekhail, G. M.; Callender, S. P.; Madkhali, O.; Bharwani, Z.; Ayyash, D.; Kobernyk, K.; Wettig, S. D.
Abstract : The effect of various inorganic and organic counterions on the aggregation behavior of gemini surfactants was examined to investigate the dominant influence of the anions on their micellization and aggregation behavior. Abstract : The effect of various inorganic and organic counterions on the aggregation behavior of gemini surfactants was examined to investigate the dominant influence of the anions on their micellization and aggregation behavior. This study included eight ethanediyl-α, ω-bis-(dimethylhexadecylammonium) gemini surfactants (GS, also known as 16–2–16) having counterions of chloride (Cl − ), bromide (Br − ), malate, tartrate, adenosine monophosphate (AMP), guanosine monophosphate (GMP), cytidine monophosphate (CMP), and uridine monophosphate (UMP). Tensiometry, conductivity and Langmuir monolayer measurements were performed to investigate the micellization and surface behaviour of each surfactant.